EGFR is not a major driver for osteosarcoma cell growth in vitro but contributes to starvation and chemotherapy resistance. Issue 1 (December 2015) - Sevelda, Florian; Mayr, Lisa; Kubista, Bernd; Lötsch, Daniela; Schoonhoven, Sushilla; Windhager, Reinhard; Pirker, Christine; Micksche, Michael; Berger, Walter
Abstract Background Enhanced signalling via the epidermal growth factor receptor (EGFR) is a hallmark of multiple human carcinomas. However, in recent years data have accumulated that EGFR might also be hyperactivated in human sarcomas. Aim of this study was to investigate the influence of EGFR inhibition on cell viability and its interaction with chemotherapy response in osteosarcoma cell lines. Methods We have investigated a panel of human osteosarcoma cell lines regarding EGFR expression and downstream signalling. To test its potential applicability as therapeutic target, inhibition of EGFR by gefitinib was combined with osteosarcoma chemotherapeutics and cell viability, migration, and cell death assays were performed. Results Osteosarcoma cells expressed distinctly differing levels of functional EGFR reaching in some cases high amounts. Functionality of EGFR in osteosarcoma cells was proven by EGF-mediated activation of both MAPK and PI3K/AKT pathway (determined by phosphorylation of ERK1/2, AKT, S6, and GSK3β). The EGFR-specific inhibitor gefitinib blocked EGF-mediated downstream signal activation. At standard in vitro culture conditions, clinically achievable gefitinib doses demonstrated only limited cytotoxic activity, however, significantly reduced long-term colony formation and cell migration. In contrast, under serum-starvation conditions active gefitinib doses were distinctly reduced while EGF promoted starvation survival. Importantly, gefitinib significantly supported the anti-osteosarcoma activities of doxorubicin and methotrexate regarding cell survival and migratory potential. Conclusion Our data suggest that EGFR is not a major driver for osteosarcoma cell growth but contributes to starvation- and chemotherapy-induced stress survival. Consequently, combination approaches including EGFR inhibitors should be evaluated for treatment of high-grade osteosarcoma patients.